BLS courses for refugees are feasible and induce commitment towards lay rescuer resuscitation. (10th July 2021) - Schnaubelt, Sebastian; Schnaubelt, Benedikt; Pilz, Arnold; Oppenauer, Julia; Yildiz, Erdem; Schriefl, Christoph; Ettl, Florian; Krammel, Mario; Garg, Rakesh; Niessner, Alexander; Greif, Robert; Domanovits, Hans; et al.
Abstract: Background: High‐quality Basic Life Support (BLS), the first step in the Utstein formula for survival, needs effective education for all kinds of population groups. The feasibility of BLS courses for refugees is not well investigated yet. Methods: We conducted BLS courses including automated external defibrillator (AED) training for refugees in Austria from 2016 to 2019. Pre‐course and after course attitudes and knowledge towards cardiopulmonary resuscitation (CPR) were assessed via questionnaires in the individuals' native languages, validated by native speaker interpreters. Results: We included 147 participants (66% male; 22 [17‐34] years; 28% <18 years) from 19 countries (74% from the Middle East). While the availability of BLS courses in the participants' home countries was low (37%), we noted increased awareness towards CPR and AED use after our courses. Willingness to perform CPR increased from 25% to 99%. A positive impact on the participants' perception of integration into their new environment was noted after CPR training. Higher level of education, male gender, age <18 years and past traumatizing experiences positively affected willingness or performance of CPR. Conclusion: BLS education for refugees is feasible and increases their willingness to perform CPR in emergency situations, with the potential to improve survival after cardiac arrest. Individuals with either past traumatizing experiences, higher education or those <18 years might be eligible for advanced life support education. Interestingly, these BLS courses bear the potential to foster resilience and integration. Therefore, CPR education for refuge should be generally offered and further evaluated.